The blood count as a compass to navigate in the ever-changing landscape of the carrier state of hemoglobinopathies: a single-center Italian experience - Marchesani, Silvio; Di Mauro, Margherita; Ceglie, Giulia; Grassia, Ginevra; Carletti, Michaela; Cristofaro, Rosa Carmela; Cossutta, Matilde; Curcio, Cristina; Palumbo, Giuseppe (Frontiers in Pediatrics, 2023)
Results: We evaluated 65 patients: 9 patients with negative genetic analysis and 56 with positive genetic analysis. In this 2 groups hemoglobin (Hb) and Red blood cells Distribution Width (RDW) values didn't prove to be significant. On the other hand, mean corpuscular volume (MCV), red blood cells (RBC), reticulocyte count and mean corpuscular volume of reticulocytes (MCVr), were statistically significantly different in the two groups. Moreover, in the group of patients with positive genetic tests we observed specific genetic findings associated with different HPLC results, in particular 13 patients with positive genetic analysis had normal HPLC findings.Discussion: In this study we have shown that HPLC, although being a very useful first-level test, has some limitations and some patients have a negative HPLC despite having a positive genetic analysis. In addition to low levels of Hb and HPLC alterations, other parameters may be suggestive of underlying mutations in the globin genes. Therefore, we propose complete blood cell count as a widely available parameter to perform targeted genetic analyses to avoid not identifying rare hemoglobinopathies.